(3GdQhVI GdQjG ajef Oaf HOGQjGs - (3YHO GdQMef Hf eMeO Hf eMeO GdYeGOi GdMfaj GdOeTbjs; (3GHf eMeO Hf CMeO Hf GdMdHj GdHSWGej, TeS GdOjf GHf GdCWYGfj,J (B807 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3GdMeO ddg GdPi fhY dgPg GdCeh CSHGH GdNjQGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B330s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B147 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B447) s
Keywords: (3GdJGQjNs